Random pattern sub-clavicular flap in digital degloving injuries: an alternative in the reconstructive ladder - Azcárate-Varela, José A.; Prieto-Vargas, Valentina; Chavez-Serna, Enrique; Fattel-Servin, Omar S.; Martínez-Wagner, Rogelio (International Surgery Journal, 2023)
Degloving soft tissue detachment injuries occur when the skin and subcutaneous tissue detach from the underlying structures, affecting the skin coverage. The hand is usually the most frequent affected site. In digital lesions, the best results are obtained by revascularization; nevertheless, this procedure is challenging for the surgeon. Random pattern flaps represent an effective alternative for the treatment of these devastating lesions. We present two clinical cases with digital degloving injury from the proximal phalanx. Both cases required reconstructive surgery in 2 stages, using a successful random pattern sub-clavicular flap. This article aims to share the results of using this method as another reconstructive option with good results. After an average follow-up of 8 months in both cases, adequate skin coverage and functionality of the finger treated with the described flap was observed. Patient A presents a finger with proper healing and functionality. Patient B at 10 months, presents a thumb with adequate length for clamping and opposition. Sub-clavicular flap is an excellent reconstructive alternative for digital degloving injuries where revascularization is unattainable, providing good skin coverage and functionality and being a reproducible outpatient procedure.